Delayed adjustable sutures: a multicentred clinical review. Issue 9 (24th June 2010) - Robbins, S L; Granet, D B; Burns, C; Freeman, R S; Eustis, H S; Yafai, S; Cruz, F; Danylyshyn-Adams, K; Langham, K
Abstract : Purpose: To characterise the results of the largest patient series to date undergoing closed conjunctival delayed adjustable suture techniques. Methods: A multicentre retrospective review of 440 operations (patients aged 10–91 years) by five surgeons at four centres were evaluated for surgical outcomes associated with the delayed adjustable suture technique. Results: 26% (116 of 440) of all patients required postoperative manipulation, with individual surgeon rates ranging from 13% to 56%. The majority of these patients did not complain of diplopia in target gaze and/or had satisfactory cosmetic improvement as evaluated at the 1–3 months follow-up visit (84%). Transient complications included dellen, poor conjunctival appearance, filamentary keratitis, infection, granuloma, exposed suture and corneal abrasion. Serious complications were rare. Conclusions: This large multicentred series characterises the closed conjunctival delayed adjustable suture technique for the correction of strabismus. It may present some significant advantages to more traditional adjustable suture techniques.